Large Energy Storage Systems Handbook - Barnes, Frank S.; Levine, Jonah G. (Mechanical and Aerospace Engineering Series, 2011)
Reviewing several ways in which large amounts of energy can be stored so that it may be deployable by utilities, this handbook covers major topics including pumped hydroelectric systems, compressed air, and batteries. By considering the perspective of developers, planners, and legislators as well as engineers tasked with assessing and developing real energy storage systems, readers will find the information they need to make economic and practical decisions concerning renewable energy. Chapters on modeling for integration of wind and solar energy into the grid, hydrogen generation and storage, and thermal energy storage are included.